Estudo do comportamento tribológico do par liga BABBITT – aço ABNT 1045 em função da rugosidade e da espessura do revestimento - Rafael Martins Ribeiro (2019)
Babbitt, also known as patent metal or white metal, is a soft alloy widely used in sliding bearings that work in contact with steel, and has as base elements tin or lead, as well as intermetallic compounds usually formed by antimony and copper. Its morphology is varied according to the amount of each element present in the chemical composition of the alloy and according to the processing. The aim of this work was to evaluate the influence of the parameters roughness and thickness of a Babbitt coating on the tribological behavior of the alloy when in contact with ABNT 1045 steel. Pin-on-disk tests were performed using ABNT 1045 steel pins and Babbitt-coated ABNT 1045 steel test specimens simulating the contact of a shaft on a Babbitt-coated bearing. The roughness and the thickness of the coating were varied in three levels, in order to observe the behavior in relation to the friction and the wear with the modification of these variables. It was also carried out the characterization of the coating (Babbitt alloy), the substrate and the test specimens tested by means of hardness and microhardness tests, profile of wear tracks, elemental chemical composition analysis by scanning electron microscopy of the phases and the intermetallics formed, besides the tracks tested. In the tests that used test specimens with the smallest roughness within the analyzed range, an increase of 0.05 ± 0.02 to 0.46 ± 0.06 in the friction coefficient occurred when the coating thickness was raised from 0.45 ± 0.07 mm for 1.08 ± 0.17 mm. The highest coefficient of friction was observed in the test of the specimen with a higher coating thickness (1.08 ± 0.17 mm) and lower roughness (0.47 ± 0.01 μm), the highest wear volume was recorded in the test with the highest coating thickness and roughness (1.08 ± 0.17 mm and 1.29 ± 0.20 m, respectively) and the lowest wear volume and friction coefficient were obtained by the test performed in the specimen with the least roughness (0.43 ± 0.03 μm) and medium coating thickness (0.45 ± 0.07 mm).